MENGATASI BULLYING DI KAMPUNG CIMANGGIS UNTUK MENJAGA KESEJAHTERAAN PSIKOLOGIS MELALUI POLA ASUH ORANG TUA - Ridho Fadhilah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Bullying is a social issue that has significant impacts on adolescents’ psychological well-being and occurs not only in school environments but also within communities. This phenomenon is also observed in Kampung Cimanggis, where bullying behaviors are often perceived as a normal part of daily interactions. This study aims to examine the phenomenon of bullying, identify its contributing factors, and analyze the role of parenting styles in its prevention and intervention. This study employs a descriptive qualitative approach using in-depth interviews with adolescents involved as both perpetrators and victims of bullying, as well as their parents. The findings indicate that bullying is influenced by social environmental factors, differences in social status, and inappropriate parenting practices, particularly authoritarian parenting and limited family communication. The forms of bullying identified include verbal, physical, and cyberbullying, which result in decreased self-confidence, increased anxiety, and difficulties in social relationships. Furthermore, the study reveals that democratic parenting plays a crucial role in preventing and addressing bullying through open communication, emotional support, and the development of empathy among adolescents. Therefore, a family-based approach can be considered an effective strategy in creating a safe and supportive environment for adolescents’ psychological well-being